2017
DOI: 10.1002/cphc.201601285
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐Metal Tungsten Oxide Photoanode Materials Made by Pulsed‐Laser in Liquids Synthesis

Abstract: Globally scalable sunlight-driven devices that convert solar energy into storable fuels will require efficient light absorbers that are made of non-precious elements. Suitable photoanode materials are yet to be discovered. Here we utilised the timesaving nature of pulsed-laser in liquids synthesis and prepared a series of neat and mixed-metal tungsten oxide photoanode materials to investigate the effect of ad-metals on optical and photocurrent generation properties. We obtained sub-µm-sized materials with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…After loading CoPi cocatalyst onto WO 3 , the Faraday efficiency for PEC oxygen evolution increases from 61 to 100%, indicating that the formation of peroxide on the CoPi/WO 3 photoanode was completely inhibited . In addition, a series of mixed‐metal WO 3 photoanodes were prepared by pulsed‐laser‐in‐liquids synthesis to investigate the effect of metal addition on optical and PEC activity . It was found that the mixed‐metal WO 3 photoanode with 5% Fe or Ni exhibited the best water oxidation performance.…”
Section: Heterogeneous Water Oxidation Catalystsmentioning
confidence: 99%
“…After loading CoPi cocatalyst onto WO 3 , the Faraday efficiency for PEC oxygen evolution increases from 61 to 100%, indicating that the formation of peroxide on the CoPi/WO 3 photoanode was completely inhibited . In addition, a series of mixed‐metal WO 3 photoanodes were prepared by pulsed‐laser‐in‐liquids synthesis to investigate the effect of metal addition on optical and PEC activity . It was found that the mixed‐metal WO 3 photoanode with 5% Fe or Ni exhibited the best water oxidation performance.…”
Section: Heterogeneous Water Oxidation Catalystsmentioning
confidence: 99%
“…To provide a solution to most of the above problems, the laser ablation synthesis in solution (LASiS) has been intensely applied and optimized in the last years, resulting in a large library of nanomaterials, [23–28] that includes various equilibrium and nonequilibrium nanoalloys like Fe−Mn, [29] Ag−Cu, [30] Pt−Cu, [31] Co−Al, [32] Au−Fe, [18,33] Ag−Fe, [34] Ag−Co, [35] as well as ternary, quaternary and quinary systems [36] or high‐entropy alloys [37] . The LASiS is scalable up to g/h of NPs, [38] is amenable of automatization and can be controlled also remotely with a PC or a smartphone, [39] thus reducing all risks connected to the laser sources, harmful or explosive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed lasers are powerful tools for the time-efficient preparation and/or modification of functional materials. Recent investigations have shown that laser-modified TiO 2 particles can be used to improve the light-driven water splitting to form hydrogen or rhodamine B degradation . Irradiation by ns–532 nm pulses yielded sub-micrometer TiO 2 spheres, SMS .…”
mentioning
confidence: 99%